KRIMINALISASI MATCH FIXING DALAM PERTANDINGAN SEPAKBOLA DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 1980 TENTANG TINDAK PIDANA SUAP - Alexzander Rinaldy; Dian Andriawan Daeng Tawang (Jurnal Hukum Adigama, 2018)
The current football competition has changed because it began to be infiltrated by organized criminals, especially in match manipulation and match fixing. Setting scores and match manipulation as a global threat in the world of football. The problem faced in writing this essay is how to criminalize match fixing in soccer matches in Indonesia based on Law Number 11 of 1980 on the Crime of Bribery. The research method used in this research is normative legal research that is research which gives systematic explanation of rules governing a certain legal category, analyze the relation between regulation explain difficulty area and may predict future development. The results showed that the criminalization of match fixing in Indonesian soccer matches based on Law Number 11 of 1980 on the Crime of Bribery was threatened with a criminal sanction although bribes in the private sector can’t be regarded as an act of corruption because they do not belong to the category of corruption based on Corruption Act. This means that it does not mean it has no impact at all in enforcing the rule. In fact, the non-regulation of bribery in the private sector in Corruption Law is related to the actors who can eradicate and enforce the provisions. Bribes (as well as corruption in general) in the private sector have brought so many bad impacts on the business sector including in football matches.